Early childhood education and care educators supporting parent-child relationships: a systematic literature review. Issue 4 (2nd October 2017) - O'Connor, Amanda; Nolan, Andrea; Bergmeier, Heidi; Hooley, Merrilyn; Olsson, Craig; Cann, Warren; Williams-Smith, Janet; Skouteris, Helen
Abstract: Building strong relationships between children and parents is vital for children's social and emotional development. A majority of children attend early childhood education and care (ECEC) settings where they experience a range of relationships (educator–child, educator–parent, parent–child). Educators build relationships with children and parents, yet their influence on parent–child relationships is not well understood. Therefore, an evaluation of interventions/programs designed to promote parent–child relationships in ECEC settings (long day care, occasional care and preschool) and a range of settings (play groups, community groups and health centres) was conducted. The search revealed 21 peer-reviewed studies and seven interventions: two conducted in ECEC settings and five in a range of parent–child support settings. All studies reported intervention efficacy, yet none examined educators' influence on parent–child relationships. Investigation into current educator practices is recommended to ensure educators are supported to promote and nurture parent–child relationships, consequently strengthening children's social and emotional development.